Preparation method and application of Fe / CoAl2O4 nano powder
By mixing FE in the COAL2O4 catalyst, the FE/Coal2O4 nano powder is prepared, the problem of high activation energy and low catalytic activity of the COAL2O4 catalyst, which significantly improves the catalytic activity and denitration efficiency of the NH3-SCR reaction.
Patent Information
- Application Number
- CN202411468250.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-24
AI Technical Summary
Pure CoAl2O4 spinel catalysts have problems with high activation energy and relatively low catalytic activity in NH3-SCR reaction.
By doping the transition metal FE and prepare the Fe/Coal2O4 nanowe, change the crystal structure, electronic structure and surface nature of the catalyst, thereby improving the catalytic activity.
Fe/CoAl2O4 nanopowder shows better catalytic activity than CoAl2O4 above 160°C, and the NOx conversion rate remains above 80% at 290°C, greatly improving the denitrification efficiency.
Smart Images

Figure CN119346111A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of Fe / CoAl2O4 nano powder, belonging to the technical field of selective catalytic reduction. Background Art
[0002] With the development of economy and the continuous progress of society, the demands of various industries have also increased. The development of high-tech has promoted the convenience of production, transportation and other aspects of life. However, it is inevitable that the increase of industrial chain and production capacity will also bring pressure on the environment and ecology. People will feel the adverse effects of environmental pollution most directly. NO widely exists in industrial and mobile pollution sources. X Due to its high harmfulness and universal existence, it has naturally become a top priority for people to study and eliminate.
[0003] The most common denitrification methods used in industry today are Selective Non-Catalytic Reduction (SNCR) and Selective Catalytic Reduction (SCR). Selective catalytic reduction (SCR) NOx is currently the most widely used and effective denitrification method. It has low secondary pollution, high denitrification efficiency, and mature technology. It has been widely used in the industrial field and has attracted more and more attention from the public for research.
[0004] High-temperature SCR is usually carried out under high-temperature conditions above 300°C. The stability of the spinel oxide catalyst structure and its good adaptability to high-temperature denitration reaction conditions enable it to operate stably for a long time under high-temperature SCR conditions, making the spinel oxide catalyst a candidate material for high-temperature SCR applications. As a spinel oxide catalyst, CoAl2O4 exhibits high catalytic activity and selectivity in the SCR process, which helps to improve denitration efficiency and reduce the generation of undesirable side reaction products.
[0005] However, pure CoAl2O4 spinel catalysts have the limitations of high activation energy and relatively low catalytic activity in the NH3-SCR reaction. In order to overcome these limitations and improve the catalytic performance, an effective strategy is to change the crystal structure, electronic structure and surface properties of the catalyst by doping with transition metals (such as Fe), thereby changing the physicochemical properties of the catalyst and improving the denitrification efficiency of the catalyst. Summary of the invention
[0006] In order to solve the problems existing in the existing CoAl2O4 spinel catalysis, one of the purposes of the present invention is to provide a method for preparing Fe / CoAl2O4 nanopowder, comprising the following steps:
[0007] (1) Dissolve Co(NO3)2·6H2O and Al(NO3)3·9H2O in deionized water to obtain a mixed solution I, and add a CTAB activator to the mixed solution I to obtain Co and Al precursor solutions.
[0008] (2) Using NaOH solution to adjust the pH value of the Co and Al precursor solutions obtained in step (1) to obtain a mixed solution II.
[0009] (3) The mixed solution II obtained in (2) is subjected to a hydrothermal reaction to obtain CoAl2O4 material.
[0010] (4) The CoAl2O4 material obtained in step (3) is centrifuged and washed with anhydrous ethanol and deionized water to remove excess surfactant, and the obtained product is dried to obtain CoAl2O4 particles.
[0011] (5) Calcine the CoAl2O4 particles obtained in step (4) to obtain a CoAl2O4 powder sample.
[0012] (6) Dissolve Fe(NO3)3·9H2O in deionized water to obtain a Fe precursor solution.
[0013] (7) Dissolving the CoAl2O4 powder obtained in step (5) in the Fe precursor solution obtained in step (6), stirring and ultrasonically treating the mixture sufficiently, to obtain a Fe / CoAl2O4 material.
[0014] (8) The Fe / CoAl2O4 nanopowder material obtained in step (7) is centrifuged and washed with anhydrous ethanol and deionized water to remove excess surfactant, and the obtained product is dried to obtain Fe / CoAl2O4 particles.
[0015] (9) Grinding the Fe / CoAl2O4 particles obtained in step (7) into powder and calcining to obtain Fe / CoAl2O4 nanopowder.
[0016] Preferably, deionized water as a solvent in step (1) does not participate in the reaction, so there is no special requirement for the amount used, and it is only necessary to fully dissolve Co(NO3)2·6H2O and Al(NO3)3·9H2O.
[0017] Preferably, in step (1), the molar ratio of Co(NO3)2·6H2O to Al(NO3)3·9H2O is 1:2, and the mass ratio of the CTAB active agent to the mixed solution I is 0:100 to 10:100.
[0018] Preferably, the pH value of solution II in step (2) is 9-11.
[0019] Preferably, the temperature of the hydrothermal reaction in step (3) is 160-180° C., and the reaction time is 16-20 h.
[0020] Preferably, in step (4) and step (8), the centrifugal speed is 8000-10000 rpm, the centrifugal time is 10-15 min, and the washing is three times, the first washing is with deionized water, the second washing is with anhydrous ethanol, and the third washing is with deionized water; the drying temperature is 60-80°C, and the drying time is 6-8 h.
[0021] Preferably, the temperature of the tubular furnace calcination in step (5) and step (9) is 700-900° C., and the calcination time is 4-6 hours.
[0022] Preferably, in step (6), the amount of Fe(NO3)3·9H2O added is 1 to 13 g per 100 ml of deionized water.
[0023] Preferably, the amount of CoAl2O4 powder added to the Fe precursor solution in step (7) is 0.1 to 2 g.
[0024] Preferably, the ultrasonic treatment time in step (7) is 2 to 6 hours.
[0025] Another object of the present invention is to provide an application of the Fe / CoAl2O4 nanopowder prepared by the method in the catalytic activity performance of NH3-SCR low-temperature reaction.
[0026] Beneficial Effects of the Invention
[0027] (1) The Fe / CoAl2O4 nanopowder disclosed in the present invention is loaded with transition metal Fe on the basis of CoAl2O4, which greatly improves its catalytic activity and shows better performance than CoAl2O4 at above 160°C. When the temperature is set to 290°C, the NOx conversion rate is maintained at above 80%, greatly improving the denitrification efficiency.
[0028] (2) The Fe / CoAl2O4 nanopowder disclosed in the present invention has good crystallinity and a particle size of nanometer level.
[0029] (3) The preparation process of the Fe / CoAl2O4 nanopowder disclosed in the present invention is simple, requires few types of raw materials, is simple and convenient, and has low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 XRD of Fe / CoAl2O4 particles prepared in Example 1 and CoAl2O4 powder prepared in Comparative Example 1.
[0031] Figure 2 This is a scanning electron microscope image of the Fe / CoAl2O4 particles prepared in Example 1.
[0032] Figure 3 These are transmission electron microscope images of the Fe / CoAl2O4 particles prepared in Example 1, wherein Figure a is a HAADF-STEM image of Fe-CoAl2O4, and Figure b is a HRTEM image of Fe-CoAl2O4.
[0033] Figure 4 This is the SEM image of the CoAl2O4 powder prepared in Comparative Example 1.
[0034] Figure 5 Schematic diagram of the device for testing the denitrification performance of the catalyst.
[0035] Figure 6 This is a diagram showing the catalytic activity of the Fe / CoAl2O4 particles prepared in Example 1 and the CoAl2O4 powder prepared in Comparative Example 1 for the NH3-SCR low-temperature reaction. DETAILED DESCRIPTION
[0036] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following embodiments are only simple examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0037] Example 1
[0038] A method for preparing Fe / CoAl2O4 nanopowder comprises the following steps:
[0039] (1) Dissolve 0.01 mol of Co(NO3)2·6H2O, 0.02 mol of Al(NO3)3·9H2O and 2 g of CTAB activator in 100 ml of deionized water and stir on a magnetic stirrer for 2 h to obtain Co and Al precursor solutions.
[0040] (2) Add NaOH solution to the Co and Al precursor solutions in step (1) and stir evenly until the pH value of the solution is 11 to obtain a mixed solution.
[0041] (3) Pour the mixed solution obtained in (2) into a reaction kettle, close the kettle and place it in an oven for hydrothermal reaction at 180° C. for 18 h to obtain CoAl 2 O 4 material.
[0042] (4) The CoAl2O4 material obtained in step (3) was washed with deionized water, anhydrous ethanol, and deionized water in this order, with a centrifugal speed of 8000 rpm and a centrifugal time of 15 min to remove excess surfactant, and the obtained product was dried in a drying oven at 60°C for 6 h to obtain CoAl2O4 particles.
[0043] (5) The CoAl2O4 particles obtained in step (4) were calcined in a tube furnace at 800°C for 5 h to obtain CoAl2O4 powder.
[0044] (6) Dissolve 10 g of Fe(NO3)3·9H2O in 100 ml of deionized water to obtain an Fe precursor solution.
[0045] (7) The CoAl2O4 powder obtained in step (5) is dissolved in the Fe precursor solution obtained in step (6), and the mixture is stirred and ultrasonically treated for 2 h to obtain a Fe / CoAl2O4 material.
[0046] (8) The Fe / CoAl2O4 material obtained in step (7) was washed with deionized water, anhydrous ethanol, and deionized water in this order, with a centrifugal speed of 8000 rpm and a centrifugal time of 15 min to remove excess surfactant, and the obtained product was dried in a drying oven at 60°C for 6 h to obtain Fe / CoAl2O4 particles.
[0047] Figure 2 This is the SEM image of Fe / CoAl2O4 prepared in this example. It can be seen from the image that the particle size of Fe / CoAl2O4 ranges from 40 to 70 nm.
[0048] Figure 3 This is the HRTEM image corresponding to Fe / CoAl2O4. The nanoparticles with a lattice spacing of 0.248nm belong to the (311) main crystal plane of cobalt aluminum spinel, while the lattice fringe spacing of 0.252nm is caused by lattice distortion after the addition of iron ions.
[0049] Example 2
[0050] A method for preparing Fe / CoAl2O4 nanopowder comprises the following steps:
[0051] (1) Dissolve 0.02 mol of Co(NO3)2·6H2O and 0.04 mol of Al(NO3)3·9H2O in 100 mL of deionized water and stir on a magnetic stirrer for 2 h to obtain Co and Al precursor solutions.
[0052] (2) Add NaOH solution to the Co and Al precursor solutions in step (1) and stir evenly until the pH value of the solution is 9 to obtain a mixed solution.
[0053] (3) Pour the mixed solution obtained in (2) into a reaction kettle, close the kettle and place it in an oven for hydrothermal reaction at 160° C. for 20 h to obtain CoAl 2 O 4 material.
[0054] (4) The CoAl2O4 material obtained in step (3) was washed with deionized water, anhydrous ethanol, and deionized water in this order, with a centrifugal speed of 10000 rpm and a centrifugal time of 10 min to remove excess surfactant, and the obtained product was dried in a drying oven at 80°C for 8 h to obtain CoAl2O4 particles.
[0055] (5) The CoAl2O4 particles obtained in step (4) were calcined in a tube furnace at 800°C for 5 h to obtain CoAl2O4 powder.
[0056] (6) Dissolve 1 g of Fe(NO3)3·9H2O in 100 ml of deionized water to obtain a Fe precursor solution.
[0057] (7) The CoAl2O4 powder obtained in step (5) is dissolved in the Fe precursor solution obtained in step (6), and the mixture is stirred and ultrasonically treated for 6 h to obtain a Fe / CoAl2O4 material.
[0058] (8) The Fe / CoAl2O4 material obtained in step (7) was washed with deionized water, anhydrous ethanol, and deionized water in this order, with a centrifugal speed of 10000 rpm and a centrifugal time of 10 min to remove excess surfactant, and the obtained product was dried in a drying oven at 60°C for 6 h to obtain Fe / CoAl2O4 particles.
[0059] The performance of the Fe / CoAl2O4 particles prepared in this example is similar to that in the example.
[0060] Comparative Example 1
[0061] As a comparison, the difference between this comparative example 1 and example 1 is that the CoAl2O4 powder sample has not been subjected to Fe 2+ The specific steps of impregnation are:
[0062] (1) Dissolve 0.01 mol of Co(NO3)2·6H2O, 0.02 mol of Al(NO3)3·9H2O and 2 g of CTAB activator in 100 ml of deionized water and stir on a magnetic stirrer for 2 h to obtain Co and Al precursor solutions.
[0063] (2) Add the Co and Al precursor solutions of step (1) into the NaOH solution and stir evenly until the pH value of the solution reaches 11.
[0064] (3) Pour the mixed solution obtained in (2) into a reaction kettle, close the kettle and place it in an oven for hydrothermal reaction at 180° C. for 18 h to obtain CoAl 2 O 4 material.
[0065] (4) The CoAl2O4 material obtained in step (3) was washed with deionized water, anhydrous ethanol, and deionized water in this order, with a centrifugal speed of 8000 rpm and a centrifugal time of 15 min to remove excess surfactant, and the obtained product was dried in a drying oven at 60°C for 6 h to obtain CoAl2O4 particles.
[0066] (5) The CoAl2O4 particles obtained in step (4) were calcined in a tube furnace at 800°C for 5 h to obtain CoAl2O4 powder.
[0067] The SEM image of the CoAl2O4 powder prepared in this comparative example is as follows Figure 4 As shown in the figure, it can be seen that the particle size range of CoAl2O4 is 50-90nm, and its particle size is larger than that of Fe / CoAl2O4 prepared in Example 1.
[0068] The Fe / CoAl2O4 particles prepared in Example 1 and the CoAl2O4 powder prepared in Comparative Example 1 were subjected to XRD test. The results are as follows: Figure 1 As shown, from Figure 1 It can be seen that the upper curve is the XRD spectrum corresponding to CoAl2O4 powder, and the lower one is the Fe / CoAl2O4 particle. Compared with CoAl2O4, the peak of Fe / CoAl2O4 is sharper and has better crystallinity. The peak positions of the main crystal directions (311) and (440) are obviously moved to the left. This is because Fe 2+ The radius is larger than Co 2+ , which also shows that Fe 2+ Successfully substituted into the crystal structure.
[0069] Specific application test:
[0070] The Fe / CoAl2O4 particles prepared in Example 1 and the CoAl2O4 powder prepared in Comparative Example 1 were placed in Figure 5 In the device for testing the denitrification performance of the catalyst shown in the figure, NO x Catalytic performance test; the entire test device consists of three parts: simulated flue gas, catalytic reaction, outlet gas detection and tail gas absorption. The simulated flue gas part is composed of NO, NO2, NH3, O2 and N2. The flow of NO, NO2, NH3, O2 and N2 is regulated by a mass flow meter. The quartz reaction tube is placed in a programmed temperature heating furnace, and the reaction gas after flow control is fully mixed in the mixing chamber and then placed in the reaction tube. The reaction tube is filled with 0.5g of catalyst (Fe / CoAl2O4 particles and CoAl2O4 powder, respectively), and the reaction gas is purified by the catalyst. The reacted gas directly enters the gas pool, and the peak value of the corresponding gas is output through the infrared spectrum signal value, and the concentration value of each gas is converted, and the tail gas is directly passed into the tail gas absorption liquid for absorption and purification.
[0071] Figure 6 The catalytic activity performance line graph of Fe / CoAl2O4 and CoAl2O4 for NH3-SCR low temperature reaction. Doping Fe in CoAl2O4 greatly improves the denitrification efficiency. More specifically, it performs better than CoAl2O4 above 160°C. When the temperature is set to 290°C, the NOx conversion rate remains above 80%. NH3 is more easily oxidized to NOx at high temperatures, resulting in a slight decrease in the NOx conversion rate afterwards. Moreover, the N2 selectivity of Fe / CoAl2O4 is better than that of CoAl2O4. First, Fe doping improves the specific surface area and active Co 2+ The number of Fe and the acidic centers of CoAl2O4 spinel catalysts all contribute to improving the low-temperature SCR activity. Second, Fe doping lengthens the chemical bonds of CoAl2O4, making it easier for Fe / CoAl2O4 to adsorb the reaction gas. The easier oxidative dehydrogenation process can promote NH3-SCR. Therefore, Fe / CoAl2O4 exhibits higher NH3-SCR performance than CoAl2O4.
Claims
1. A method for preparing Fe / CoAl2O4 nanopowder, characterized in that: The following steps are involved: (1) dissolving Co(NO3)2·6H2O, Al(NO3)3·9H2O and NH4SO4 in deionized water to obtain a mixed solution I, and adding a CTAB activator to the mixed solution I to obtain a Co and Al precursor solution; (2) adjusting the pH value of the Co and Al precursor solutions obtained in step (1) with a NaOH solution to obtain a mixed solution II; (3) subjecting the mixed solution II obtained in step (2) to a hydrothermal reaction to obtain a CoAl2O4 material; (4) washing the CoAl2O4 material obtained in step (3) by centrifugation with anhydrous ethanol and deionized water to remove excess surfactant, and drying the obtained product to obtain CoAl2O4 particles; (5) calcining the CoAl2O4 particles obtained in step (4) to obtain a CoAl2O4 powder sample; (6) dissolving Fe(NO3)3·9H2O in deionized water to obtain a Fe precursor solution; (7) dissolving the CoAl2O4 powder obtained in step (5) in the Fe precursor solution obtained in step (6), stirring and ultrasonically treating the mixture to obtain a Fe / CoAl2O4 material; (8) The Fe / CoAl2O4 nanopowder material obtained in step (7) is centrifuged and washed with anhydrous ethanol and deionized water to remove excess surfactant, and the obtained product is dried to obtain Fe / CoAl2O4 particles; (9) Grinding the Fe / CoAl2O4 particles obtained in step (7) into powder, and calcining to obtain Fe / CoAl2O4 nanopowder.
2. The method for preparing Fe / CoAl2O4 nanopowder according to claim 1, characterized in that: In step (1), the molar ratio of Co(NO3)2·6H2O to Al(NO3)3·9H2O is 1:2, and the mass ratio of the CTAB active agent to the mixed solution I is 0:100 to 10:
100.
3. The method for preparing Fe / CoAl2O4 nanopowder according to claim 1, characterized in that: The pH value of solution II in step (2) is 9-11.
4. The method for preparing Fe / CoAl2O4 nanopowder according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step (3) is 160-180° C., and the reaction time is 16-20 h.
5. The method for preparing Fe / CoAl2O4 nanopowder according to claim 1, characterized in that: In step (4) and step (8), the centrifugal speed is 8000-10000 rpm, the centrifugal time is 10-15 min, and the washing is three times, the first washing is with deionized water, the second washing is with anhydrous ethanol, and the third washing is with deionized water; the drying temperature is 60-80° C., and the drying time is 6-8 h.
6. The method for preparing Fe / CoAl2O4 nanopowder according to claim 1, characterized in that: In step (5) and step (9), the temperature of the tubular furnace calcination is 700-900° C., and the calcination time is 4-6 hours.
7. The method for preparing Fe / CoAl2O4 nanopowder according to claim 1, characterized in that: In step (6), the amount of Fe(NO3)3·9H2O added is 1 to 13 g per 100 ml of deionized water.
8. The method for preparing Fe / CoAl2O4 nanopowder according to claim 1, characterized in that: In step (7), the amount of CoAl2O4 powder added to the Fe precursor solution is 0.1 to 2 g.
9. The method for preparing Fe / CoAl2O4 nanopowder according to claim 1, characterized in that: The ultrasonic treatment time in step (7) is 2 to 6 hours.
10. Application of the Fe / CoAl2O4 nanopowder prepared by the method according to any one of claims 1 to 8 in the catalytic activity performance of NH3-SCR low temperature reaction.